A primer on risk assessment modelling : - Fazil, Aamir M. (FAO, 2006)
This paper is written as an introduction to the concepts of microbial risk assessment in general, but with a seafood focus and greater emphasis on the quantitative approach. The risk of food-borne disease is a combination of the likelihood of exposure to the pathogen, the likelihood of infection or intoxication resulting in illness and the severity of the illness. In a system as complex as the production and consumption of food, many factors affect both the likelihood and severity. To manage food safety effectively, a systematic means of examining these factors is necessary.